Estudo de Impacto Ambiental (EIA): o EIA como principal meio de prevenção à degradação ambiental - LOPES, Darcilene Ramos (2019)
This paper aimed do show the importance of the Environmental Impact Assessment (EIA), as a previous study, to prevent environmental degradation caused by a conception of enterprises which are potentially damaging to environment, denoting its main function. Demonstrated it is, the great importance of EIA, which since its conception permits that environmental degradations are foreseen and previously studied, preventing as to negative impacts that may be implanted by a certain enterprise, being these impacts partially reversible before the technics of impact absorption. This paper also exposes the systematic of creation and application of EIA, on the one hand by the view of Human Science of Law, that before any protective function which the EIA may furnish, sticks to legal formalities for its conception, on the other hand in the world of phenomena that daily surrounds us. The EIA is considered an indispensable requisite when we propose enterprises of great impact for the process of license concession of it, becoming this way a tool for it. With the proposed aim to demonstrate preventively the damages to be caused to environment, it is indispensable the concept of it, what is clearly defined as the number of conditions, laws, influences and interactions of physical, chemical and biological order, which allows, houses and rules life in all its forms, being so, defined in law. In the same way, it becomes not less indispensable the definition of environmental impact, starting factor of high importance for the creation of EIA. Being thus noticed, in a less profound way as, all alteration of chemical or biological order of the aspects that change the environment, scheming this way the environmental impact as the great factor generating the Study of Environmental Impact, which is the main aim of this paper.